(untitled) (Revista Latino-Americana de Enfermagem, 2002)
This study analyzes titles of research works published in a nursing journal in 1997 and 1998. Data were collected through forms and organized by using the EPI-INFO 6.0 computer program. The analysis was based on recent national and international literature concerning the analysis of research reports. Results, which have been disposed in tables, showed that most of the analyzed articles presented a partly adequate titles in relation to variables, studied populations and/or key words It was concluded that the evaluation of titles in nursing research still requires more attention since a large number of databases aused by researchers only publicize research work means of its titles.